2022
DOI: 10.3390/nu14214594
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of MTRR and MTHFR Gene Polymorphisms in Colorectal Cancer Survival

Abstract: Background: Paradoxically epidemiological data illustrate a negative relationship between dietary folate intake and colorectal cancer (CRC) risk. The occurrence and progression of CRC may be influenced by variants in some key enzyme coding genes in the folate metabolic pathway. We investigated the correlation between genetic variants in methionine synthase reductase (MTRR) and methylenetetrahydrofolate reductase (MTHFR) and CRC survival. Methods: This study used data collected from the Newfoundland Familial Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In a previous publication from our group [22], with a totally different cohort of neuroblastoma patients, we already found that this variant was correlated with poorer overall survival in both normal and amplified MYCN patients. It is not clear yet if these results are through a direct effect of the enzyme on the chemotherapeutic drugs, or related to DNA methylation and or synthesis, or a combination of all, but recent literature find similar results in different adult and pediatric cancers [18,23,24].…”
Section: Survivalmentioning
confidence: 99%
“…In a previous publication from our group [22], with a totally different cohort of neuroblastoma patients, we already found that this variant was correlated with poorer overall survival in both normal and amplified MYCN patients. It is not clear yet if these results are through a direct effect of the enzyme on the chemotherapeutic drugs, or related to DNA methylation and or synthesis, or a combination of all, but recent literature find similar results in different adult and pediatric cancers [18,23,24].…”
Section: Survivalmentioning
confidence: 99%
“…However, Baghad et al showed a statistically significant association between the MTHFR677T variant and the risk of sporadic colorectal carcinogenesis in a Moroccan population, CT genotype and its combination with TT genotype and allele T were associated with increased risk of CRC, but the pure-hybrid TT was not a protective factor. A recent study [49] showed that the MTHFR gene was associated at the genetic level with disease-free survival and CRC-specific survival in CRC patients, and the association of the gene with CRC outcome appeared to be modulated by alcohol consumption and fruit intake. Notably, Teng [42] and Haerian BS [50] studies presented a different view, stating that the MTHFR A1298C polymorphism was positively associated with susceptibility to CRC, which may be due to inconsistent genetic modeling.…”
Section: Correlation Of Mthfr Gene Polymorphisms With Colorectal Cancermentioning
confidence: 99%